UPAYA MENINGKATKAN HASIL BELAJAR PESERTA DIDIK MELALUI METODE MENGAJAR DISCOVERY LEARNING - Cicilia Dyah Sulistyaningrum Indrawati; Patni Ninghardjanti; Ulya Farras 'Abidah (Program Studi Pendidikan Administrasi perkantoran FKIP UNS, 2022)
This study aims to determine the improvement of learning outcomes and describe the learning process through the application of discovery learning methods to students of class X OTKP 1 at SMK Negeri 1 Ponorogo. This type of research is included in classroom action research with the design of Kemmis and Mc. Taggart. This study consisted of two cycles and each cycle consisted of four stages, namely planning, action, observation, and reflection. The subjects of this study were students of class X, totaling 15 people. Data was collected by using observation sheets and learning outcomes tests and reinforced by interviews and documentation. Data analysis techniques used are critical analysis techniques and comparative descriptive analysis techniques. The results showed that the learning outcomes of students in the first cycle the percentage of completeness was 73.3% (unfinished) and in the second cycle increased with the percentage of completeness of 86.67% (finish). The average score of student learning activities and teacher teaching in the first cycle both obtained a score of 2 (good enough) and in the second cycle increased with a score of 4 (very good) for student learning activities and a score of 3 (good) for teaching activities teacher. The conclusion from the results of this study is that the application of discovery learning methods can improve the learning outcomes of students in class X OTKP 1 SMK Negeri 1 Ponorogo on communication materials in the workplace.